Architectural Diversity of Submarine Lobate Deposits - McHargue, Tim R.; Hodgson, David M.; Shelef, Eitan (Frontiers in Earth Science, 2021)
Lobate deposits in deep-water settings are diverse in their depositional architecture but this diversity is under-represented in the literature. Diverse architectures result from multiple factors including source material, basin margin physiography, transport pathway, and depositional setting. In this contribution, we emphasize the impact of differing source materials related to differing delivery mechanisms and their influence on architecture, which is an important consideration in source-to-sink studies. Three well imaged subsurface lobate deposits are described that display three markedly different morphologies. All three lobate examples, two from intraslope settings offshore Nigeria and one from a basin-floor setting offshore Indonesia, are buried by less than 150 m of muddy sediment and are imaged with high resolution 3D reflection seismic data of similar quality and resolution. Distinctively different distributary channel patterns are present in two of the examples, and no comparable distributaries are imaged in a third example. Distributary channels are emphasized because they are objectively recognized and because they often represent elements of elevated fluid content within buried lobate deposits and thus influence permeability structure. We speculate that the different distributary channel patterns documented here resulted from different processes linked to source materials: 1) a lobate deposit that is pervasively channelized by many distributaries that have branched at numerous points is interpreted to result from comparatively mud-rich, stratified, turbulent flows; 2) an absence of distributaries in a lobate deposit is interpreted to result from collapse of mud-poor, turbulent flows remobilized from littoral drift; and 3) a lobate deposit with only a few, long, straight distributaries with few branching points is interpreted to be dominated by highly viscous flows (i.e., debris flows). We propose a conceptual model that illustrates the relationship between the proportion of mud in contributing flows and the relative size and runout distance of lobate deposits. We conclude that reconciling 3D seismic morphologies with outcrop observations of channels, scours, and amalgamation zones, and simple application of hierarchical schemes, is problematic. Furthermore, when characterizing unconfined deep-water deposits in the subsurface, multiple models with significant differences in predicted permeability structure should be considered.